2019
DOI: 10.1101/700351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ralstonia solanacearumdepends on catabolism of myo-inositol, sucrose, and trehalose for virulence in an infection stage-dependent manner

Abstract: The soilborne pathogen Ralstonia solanacearum (Rs) causes lethal bacterial wilt disease of tomato and many other crops by infecting host roots and then colonizing the xylem vessels. Tomato xylem sap is nutritionally limiting but it does contain sucrose and trehalose. Transcriptomic analyses revealed that Rs expresses distinct sets of catabolic pathways at low cell density (LCD) and high cell density (HCD). To investigate the links between bacterial catabolism, infection stage, and virulence, we measured the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The existence of the type III-secreted effector TPS (RipTPS) also hints at an active pathogen role in manipulating plant trehalose metabolism (Poueymiro et al 2014). However, although strain GMI1000 can grow on trehalose as a sole carbon source, this sugar is not a significant carbon source for R. solanacearum during tomato colonization and pathogenesis, and trehalose is present in xylem sap at much lower concentrations than the more palatable sucrose (Hamilton et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of the type III-secreted effector TPS (RipTPS) also hints at an active pathogen role in manipulating plant trehalose metabolism (Poueymiro et al 2014). However, although strain GMI1000 can grow on trehalose as a sole carbon source, this sugar is not a significant carbon source for R. solanacearum during tomato colonization and pathogenesis, and trehalose is present in xylem sap at much lower concentrations than the more palatable sucrose (Hamilton et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR measurement of treY, treS, and otsA expression in a treA mutant background showed that mutating trehalase did not affect expression of any of the trehalose biosynthetic pathways, suggesting trehalose synthesis is regulated independently from its degradation (data not shown). Further characterization of the DtreA mutant is reported elsewhere (Hamilton et al 2019). The DotsA and DtreY/treS/otsA strains grew as well as wild type in minimal media plus glucose at the R. solanacearum optimal growth temperature of 28°C ( Fig.…”
Section: Genetic Basis Of Trehalose Metabolismmentioning
confidence: 97%
“…Mutating any of these genes leads to a loss of T3SS gene expression, yet all three were highly downregulated in planta compared to either CPG or VDM ( Supplementary Table 4) (Zhang et al 2011;Jacobs et al 2012). Several other genes that were highly upregulated in planta in both experiments encode metabolism of sucrose or myo-inositol, two carbon sources important for R. solanacearum during infection (Lowe-Power et al 2018b;Hamilton et al 2020;Xian et al 2020). Additionally, genes involved in flagellar motility were upregulated in both experiments.…”
Section: Discussionmentioning
confidence: 97%
“…solanacearum during infection (Hamilton et al, 2020;Lowe-Power, Khokhani, et al, 2018;Xian et al, 2020). Additionally, genes involved in flagellar motility were upregulated in both experiments.…”
Section: Discussionmentioning
confidence: 99%
“…No reuse allowed without permission. R. solanacearum GMI1000 produces and secretes abundant amounts of the TreA trehalase during tomato infection, and ability to degrade trehalose contributes to bacterial fitness and virulence even though trehalose is not an important nutritional source for the pathogen (Jacobs, Babujee et al 2012, Hamilton, Steidl et al 2021. Interestingly, treating plants with the trehalase inhibitor Validamycin A increased BW resistance (Ishikawa, Fujimori et al 1996).…”
Section: Discussionmentioning
confidence: 99%